Stereo Matching Algorithm Based On Per Pixel Difference Adjustment, Iterative Guided Filter And Graph Segmentation - Hamzah, Rostam Affendi; Ibrahim, Haidi; Abu Hassan, Anwar Hasni (Elsevier Inc., 2017)
Stereo matching process is a difficult and challenging task due to many uncontrollable factors that affect the results. These factors include the radiometric variations and illumination inconsistence. The absolute differences (AD) algorithms work fast, but they are too sensitive to noise and low textured areas. Therefore, this paper proposes an improved algorithm to overcome these limitations. First, the proposed algorithm utilizes per-pixel difference adjustment for AD and gradient matching to reduce the radiometric distortions. Then, both differences are combined with census transform to reduce the effect of illumination variations. Second, a new approach of iterative guided filter is introduced at cost aggregation to preserve and improve the object boundaries. The undirected graph segmentation is used at the last stage in order to smoothen the low textured areas. The experimental results on the standard indoor and outdoor datasets show that the proposed algorithm produces smooth disparity maps and accurate results.